PENGARUH KEPEMIMPINAN DAN KOMUNIKASI KERJA TERHADAP KINERJA KARYAWAN PADA PT GLOBAL TIMUR EKSPRESS AREA KEBAYORAN LAMA - Fitrah Pratama; Anggada Bayu Seta (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The purpose of the study was to determine how much influence leadership and communication have on employee performance at PT Global Timur Ekspress Kebayoran Lama, both partially and simultaneously. The method used is a quantitative method with a sampling technique using saturated samples, and obtained a sample of 69 respondents. Data analysis using Validity Test, Reliability Test, Classical Assumption Test, Descriptive Analysis, Quantitative Analysis, Correlation Coefficient, Determination Coefficient (KD), and Hypothesis Test. The results of the study indicate that partially there is a positive and significant influence between leadership and employee performance at PT Global Timur Ekspress Kebayoran Lama. This can be proven from the simple linear regression equation Y = 18.676 + 0.567X1. The correlation value is 0.582 and the tcount value is 5.859> ttable 1.672 with a significance of 0.000 <0.05. Partially there is a positive and significant influence between communication and employee performance at PT Global Timur Ekspress Kebayoran Lama. This can be proven from the simple linear regression equation Y = 20.912 + 0.517X2. The correlation value is 0.575 and the tcount value is 5.754> ttable 1.672 with a significance of 0.000 <0.05. Simultaneously there is a positive and significant influence between Leadership and Communication on Employee Performance at T Global Timur Ekspress Kebayoran Lama. This can be proven from the multiple linear regression equation Y = 14.903 + 0.350X1 + 0.305X2. The coefficient of determination is 38.6%. And the Fcount value is 22.408> Ftable 3.16 with a significance level of 0.000 <0.05.